The Effect of STEM-Based REACT Model on Students' Critical Thinking Skills: A Meta-Analysis Study - Mulya Putra; Abdul Rahman; Ilwandri Ilwandri; Yayat Suhayat; Tomi Apra Santosa; Ringgo Putra; Sanju Aprilisia (Badan Penerbit STIEPARI Press, 2023)
This study aims to determine the effectiveness of the STEM-based REACT model on students' critical thinking skills. This research is a meta-analysis study. This study collected previous meta-analysis studies related to the STEM-based REACT model that showed gaps in the current article. The data sources in the study came from 13 national and international journals published in 2018-2019. The process of searching for data sources through the google scholar database, Eric, Wiley, Taylor of Francis, ScienceDirect, ProQuest and Hindawi. Inclusion criteria are studies on the REACT model using experimental or quasi-experimental research methods and measurement of critical thinking skills to evaluate the effect of the REACT model. The results showed that the average effect size value (ES = 0.88) with high criteria. The findings show that the application of the STEM-based REACT model has a significant effect on students' critical thinking skills. Furthermore, the effect size in this study was influenced by the level of education, learning outcomes, and student competencies. The STEM-based REACT model has a positive impact on students in encouraging their critical thinking skills.